Awareness of the dual-use dilemma in scientific research: reflections and challenges to Latin America - Flores-Coronado, Jose Alonso; Alanis-Valdez, Alondra Yamileth; Herrera-Saldivar, Maria Fernanda; Flores-Flores, Aldo Sebastian; Vazquez-Guillen, Jose Manuel; Tamez-Guerra, Reyes S.; Rodriguez-Padilla, Cristina (Frontiers in Bioengineering and Biotechnology, 2025)
The dual-use dilemma compels us to reflect on scientific responsibility, ethical regulation, and the role of society in the governance of knowledge. While science has the potential to transform the world for the better, it can also become a double-edged sword if the implications of its potential misuse are overlooked. This is particularly relevant in the life sciences, where advances can be repurposed for harmful by secondary actors. Addressing this challenge requires the development of preventive tools, biosafety and biosecurity measures specifically designed for dual-use research, and clear, up-to-date regulatory frameworks at both national and international levels. These mechanisms should aim to anticipate risks, restrict unauthorized access to sensitive information, and foster a culture of responsibility within the scientific community, without hindering the advancement of knowledge or obstructing legitimate innovation. This perspective explores the dual-use dilemma through a global lens, with a specific focus on Latin America, a region where policies and institutional awareness on dual-use risks remain limited. By analyzing illustrative case studies, existing international tools, and regional gaps, this work highlights both the obstacles and opportunities for strengthening dual-use governance in Latin American research systems.